THE ROLE OF LIPID METABOLISM IN THE DEVELOPMENT OF ENDOTHELIAL DYSFUNCTION IN DIABETIC NEPHROPATHY - Mammadzada, A.Y.; Ismayilova, Sh.G. (World of Medicine and Biology, 2023)
The purpose of the study was to study the relationship between lipid metabolism and flow-mediated dilation and endothelium-independent vascular dilation in diabetic nephropathy patients. The study included 120 patients with chronic kidney disease against the background of diabetic nephropathy. They were divided into 4 groups according to the stages of disease. The level of flow-mediated dilation in the brachial artery was determined by the hyperemic test and the level of endothelium-independent vascular dilation by the nitroglycerin test. The lipid spectrum was assessed by the level of total cholesterol, triglycerides, high-density lipoproteins, low-density lipoproteins in blood serum, as well as by calculating the atherogenic coefficient. In the 1st group, a moderate inverse relationship was determined between flow-mediated dilation and total cholesterol, triglycerides, atherogenic coefficient (respectively, r=–0.503, p
Keywords: diabetic nephropathy; flow-mediated dilation; nitroglycerine-induced vasodilation; lipid metabolism